Albumin competitively inhibits glycation of less abundant proteins - Bhonsle, Hemangi S.; Singh, Sameer Kumar; Srivastava, Ghanshyam; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Protein and Peptide Letters, 2008)
Glycation, a non-enzymatic reaction between glucose and protein is the primary cause of diabetic complications. Albumin, the most abundant plasma protein undergoes glycation both in vivo and in vitro. The influence of albumin on glycation of less abundant proteins has not been addressed. For the first time, we show that albumin competitively inhibits the glycation of less abundant proteins. This study suggests that at least in the initial stages of diabetes, albumin may protect other proteins from glycation.
Keywords: Diabetes; glucose; insulin; MALDI-TOF-MS; vascular complication

Discovery of rifampicin as a new anti-glycating compound by matrix-assisted laser desorption/ionization mass spectrometry-based insulin glycation assay - Golegaonkar, Sandeep B.; Bhonsle, Hemangi S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2010)
An in vitro insulin glycation assay was developed for screening glycation inhibitors. The assay involves the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for monitoring the formation of glycated insulin. The assay is simple, rapid and amenable for high throughput screening. Using this assay we have discovered a strong anti-glycation activity for the anti-tuberculosis drug rifampicin. These results were compared with bovine serum albumin glucose fluorescence assay. In addition, the IC(50) of rifampicin was lower than that of aminoguanidine, a known anti-glycating agent, suggesting that rifampicin is a more potent glycation inhibitor.
Keywords: AGE; aminoguanidine; antibiotic; diabetic complication; drug repositioning; IC(50)

Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification

Proteomic analysis of glycated proteins from streptozotocin-induced diabetic rat kidney - Chougale, Ashok D.; Bhat, Shweta P.; Bhujbal, Swapnil V.; Zambare, Mandar R.; Puntambekar, Shraddha; Somani, Rahul S.; Boppana, Ramanamurthy; Giri, Ashok P.; Kulkarni, Mahesh J. (Molecular Biotechnology, 2012)
Glycation of proteins leading to formation of advanced glycation end products (AGEs) has been considered as one of the important causes of diabetic nephropathy. Therefore, in this study, glycated proteins were detected by anti-AGE antibodies from kidney of streptozotocin-induced diabetic rat showing nephropathic symptoms, by using two dimensional electrophoresis and western blot analysis. These glycated proteins were identified and characterized by using combination of peptide mass finger printing and tandem mass spectrometric approaches. Glycated proteins identified included proteins from metabolic pathways, oxidative stress, cell signaling, and transport. Several of the proteins modified by glycation were involved in glucose metabolism. The extent of glycation was higher in diabetes compared to control, in the glycated proteins that were common to both control and diabetic kidney. Two dimensional electrophoresis proteins profiling of glycated proteins suggest that four of the glycated proteins were significantly up regulated in diabetes.
Keywords: AGE; Diabetes; Glucose toxicity; Nephropathy; Post-translation modification

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.

Molecules with O-acetyl group protect protein glycation by acetylating lysine residues - Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Kashinath, K.; Kesavan, Suresh K.; Bhat, Shweta; Korwar, Arvind M.; Chougale, Ashok D.; Boppana, Ramanamurthy; Reddy, D. Srinivasa; Kulkarni, Mahesh J. (RSC Advances, 2016)
Pharmaceutical intervention for reduction of advanced glycation end products (AGEs) is considered as a therapeutic strategy to attenuate the pathogenesis of diabetes. Many molecules have been reported to possess antiglycation activity, one such example is acetylsalicylic acid (aspirin). It protects proteins from glycation by acetylating the lysine residues. Therefore, in this study we have synthesized and screened molecules containing free N-acetyl, O-acetyl and acetophenone groups. All the selected molecules in this study showed glycation inhibition but interestingly, only molecules with O-acetyl but not N-acetyl and acetophenone groups were capable of acetylating lysine residue. Furthermore, we have demonstrated that pre-acetylation or aspirin treatment prior to the induction of diabetes helps in reducing HbA1c and AGE formation in the streptozotocin induced diabetic mice. Hence pre-acetylation may have an additional therapeutic efficacy of reducing AGE levels in vivo. Incorporation of O-acetyl group into anti-diabetic molecules could be a useful strategy, as it may have an additive effect in reducing AGEs. Identification of such novel acetylating agents represents a new area in the drug discovery process.

Potential dual role of eugenol in inhibiting advanced glycation end products in diabetes: proteomic and mechanistic insights - Singh, Priyanka; Jayaramaiah, Ramesha H.; Agawane, Sachin B.; Vannuruswamy, Garikapati; Korwar, Arvind M.; Anand, Atul; Dhaygude, Vitthal S.; Shaikh, Mahemud L.; Joshi, Rakesh S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J.; Thulasiram, Hirekodathakallu V.; et al. (Scientific Reports, 2016)
Medicinally important genus Ocimum harbors a vast pool of chemically diverse metabolites. Current study aims at identifying anti-diabetic candidate compounds from Ocimum species. Major metabolites in O. kilimandscharicum, O. tenuiflorum, O. gratissimum were purified, characterized and evaluated for anti-glycation activity. In vitro inhibition of advanced glycation end products (AGEs) by eugenol was found to be highest. Preliminary biophysical analysis and blind docking studies to understand eugenol-albumin interaction indicated eugenol to possess strong binding affinity for surface exposed lysines. However, binding of eugenol to bovine serum albumin (BSA) did not result in significant change in secondary structure of protein. In vivo diabetic mice model studies with eugenol showed reduction in blood glucose levels by 38% likely due to inhibition of alpha-glucosidase while insulin and glycated hemoglobin levels remain unchanged. Western blotting using anti-AGE antibody and mass spectrometry detected notably fewer AGE modified peptides upon eugenol treatment both in vivo and in vitro. Histopathological examination revealed comparatively lesser lesions in eugenol-treated mice. Thus, we propose eugenol has dual mode of action in combating diabetes; it lowers blood glucose by inhibiting a-glucosidase and prevents AGE formation by binding to epsilon-amine group on lysine, protecting it from glycation, offering potential use in diabetic management.

Proteomic insight reveals elevated levels of albumin in circulating immunecomplexes in diabetic plasma - Bhat, Shweta; Jagadeeshaprasad, Mashanipalya G.; Patil, Yugendra R.; Shaikh, Mahemud L.; Regin, Bhaskaran S.; Mohan, Viswanathan; Giri, Ashok P.; Balasubramanyam, Muthuswamy; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2016)
A Hyperglycemic condition in diabetes promotes formation of advanced glycation end products, which are known to elicit immune response and form complexes with immunoglobulins called circulating immune complexes. To investigate the involvement of advanced glycation end product (AGE)-modified proteins in the elicitation of an immune response, circulating immune complexes were isolated and proteins associated were identified and characterized. Label-free-based mass spectrometric analysis of circulating immune complexes in clinical plasma of prediabetic, newly diagnosed diabetes, and diabetic microalbuminurea revealed elevated levels of serum albumin in the circulating immune complexes, which were also observed to be AGE modified. Further, to examine the role of glycation, circulating immune complexeswere analyzed in the streptozotocin-induced diabetic mice treated with or without aminoguanidine, a prototype glycation inhibitor. Mass spectrometric analysis of circulating immune complexes showed elevated levels of serum albumin in plasma from diabetic mice over that of control animals. Aminoguanidine-treated diabetic mice displayed decreased AGE modification of plasma albumin, accompanied by a reduced level of albumin in the circulating immune complexes. In addition, elevated levels of proinflammatory cytokines such as IL-1b, IL-2, and TNF-alpha were observed in diabetes, which were reduced with aminoguanidine treatment, suggesting the involvement of glycation in the immune response.